2022
DOI: 10.1186/s12931-022-02042-5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of airway basal stem cells in lung homeostasis and regenerative medicine

Abstract: Airway basal stem cells (BSCs) in the proximal airways are recognized as resident stem cells capable of self-renewing and differentiating to virtually every pseudostratified epithelium cell type under steady-state and after acute injury. In homeostasis, BSCs typically maintain a quiescent state. However, when exposed to acute injuries by either physical insults, chemical damage, or pathogen infection, the remaining BSCs increase their proliferation rate apace within the first 24 h and differentiate to restore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 108 publications
0
17
0
Order By: Relevance
“…Indeed, our pseudotime analysis revealed that FOXJ high ciliated cells were the most terminally differentiated cell type, followed by FOXJ1 low ciliated cells, multiciliated precursors, club cells, ionocytes, and finally basal cells (which were defined as the root cells in our analysis) (42)(43)(44) (Fig. 2)(SFig.…”
Section: Primary Lung Epithelial Cells Cluster Into Six Cell Types In...mentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, our pseudotime analysis revealed that FOXJ high ciliated cells were the most terminally differentiated cell type, followed by FOXJ1 low ciliated cells, multiciliated precursors, club cells, ionocytes, and finally basal cells (which were defined as the root cells in our analysis) (42)(43)(44) (Fig. 2)(SFig.…”
Section: Primary Lung Epithelial Cells Cluster Into Six Cell Types In...mentioning
confidence: 79%
“…The lung epithelium primarily consists of fully differentiated cells, but injury can cause cells to dedifferentiate into their progenitors (41)(42)(43). We were interested to see if there were differences in cell differentiation among age cohorts or treatment status.…”
Section: Primary Lung Epithelial Cells Cluster Into Six Cell Types In...mentioning
confidence: 99%
“…IAV infection inflicted damage to the stratified layer of the airway epithelium, accompanied by an increased population of basal cells (Fig. 4d), potentially indicating a regenerative phase following the substantial loss of multiciliated cells [48][49][50] . Co-localization of IAV NP and cytokeratin may also indicate the dedifferentiation of infected cells as reported previously 51 .…”
Section: Discussionmentioning
confidence: 99%
“…4b). Basal cells, which are adult stem cells located at the base of the airway epithelium near the basement membrane, can increase in number and differentiate into multiciliated cells in the event of an injury 42 . Immunofluorescent staining of Cytokeratin 5, a marker for basal cells, revealed an increase in the number of basal cells after infection (Fig.…”
Section: Iav Causes Heightened Cellular Damage In Both Airway and Alv...mentioning
confidence: 99%
“…In the skin, the stratum corneum, formed by several layers of corneocytes embedded in extracellular lipids, protects the subjacent tissue [5]. A rapid turnover of cells at the surface is a common feature among epithelia in different tissues and allows for quick adaptation to insults and fast wound healing [6–8].…”
Section: Introduction: the Epithelium As A Barriermentioning
confidence: 99%